The Role of Real Options Theory in Capital Budgeting for Energy Projects in the Mining Industry - Khumalo, Nkosikhona (University of the Witwatersrand, Johannesburg, 2024)
Global warming and the changing weather patterns have resulted in developing and developed economies (public and private) to invest in low-carbon solutions and greenhouse gas emission reduction initiatives. The mining sector is one of the notable contributors to environmental degradation owing to its mining and processing activities, with a reported 4% to 7% greenhouse gas emissions globally (Delevingne, Glazener, Grégoir, & Henderson, 2020). Implementation of energy projects shows commitments to address climate change and global warming issues. Under the 2015 Paris Agreement, 196 parties (governments) pledged to limit global average temperatures well below 2ᵒC and to limit the temperature increase to 1.5ᵒC above pre-industrial levels (UNCC, 2024) (Delevingne, Glazener, Grégoir, & Henderson, 2020) (Bloomberg, 2017). The commitments and drive have since seen energy investments being incorporated as key strategic pillars in private, public, and state-owned businesses. This research focuses on the use of real options theory in evaluating capital intensive energy projects in the mining sector. The energy use contributes about three-quarters of greenhouse gas emissions globally (Agency, www.iea.org, 2024). The mining houses are expected to set up clear targets and implementation plans to achieve net zero by 2050. The journey to 2050 is enabled and supported by different guidelines such as GHG Protocols, Corporate Sustainability Reporting Directives, 17 Sustainable Development Goals, Intergovernmental Panel on Climate Change, Paris Agreements, Task Force on Climate-Relates on Financial Disclosures etc. Each role player is expected to devise a comprehensive and inclusive strategy to be certified net-zero by 2050. This can be achieved by developing business cases on its energy and GHG maturity journey based on actionable plans implementation and incremental intervention on a yearly basis The energy projects portfolio scope is wide, constituting among other things, energy security, alternative energies, renewables, energy management etc. However, the research case study is limited to investment valuations of energy efficiency projects for the process plant in the mining sector. Energy efficiency projects provide significant reduction in energy cost and greenhouse reduction. These projects are characterized by high capital costs and significant level of uncertainty owing to the uncertainty in policy position, policy evolution timelines, commodity prices and availability of tried and tested technical solutions. These constraints can be addressed through a risk-based approach which enables management flexibility to minimise potential business losses and improve on gains. The losses can be attributed to reputational damage affecting share prices, loss of key customers and results in high sunk costs, should projects prove to be unsuccessful. The real option theory analysis, an effective technique in resolving uncertainty and enabling managerial flexibility could be the ideal solution, given its applications in the energy domain (Fabianek, Glensk, & Madlener, 2021), (Liu, Zhang, & Zhao, 2019) to address drawbacks of traditional valuation techniques whilst meeting business objectives and climate change commitments
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Capital budgeting; Discounted cashflow; Real options; Back-Scholes model; UCTD; SDG-8: Decent work and economic growth